Communication skills of a local general practitioner in conducting preventive counseling (methodological aspect) - S. Yu. Astanina; A. M. Kalinina; R. N. Shepel; E. A. Derinova; N. A. Mikhailova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The article considers the problem of developing communicative competence of local general practitioners in preventive counseling. The study showed that the process of preventive counseling is an integration of medical diagnostic, preventive and psychologicalpedagogical activities of a local general practitioner.The paper presents the content of the doctor’s communicative competence, which is the ability and readiness to inform the patient about the examination results, to clarify information taking into account the individual patient characteristics, as well as to improve the patient’s medical adherence.The indicators of achieving the anticipated results, expressed in communicative competence development, are determined, represented by communicative skills, which make up 3/4 of the total number of skills being formed, and the doctor’s skills in medical diagnostic and preventive activities, which make up 1/4 of the total number of necessary skills.The results obtained made it possible to predict the most effective methods of preparing doctors for a brief preventive consultation and to determine the requirements for control and evaluation materials that provide an objective assessment of the development of identified skills. The obtained materials can serve as a basis for developing a methodology for developing doctor’s communicative skills in conducting preventive counseling and further quality monitoring.